Technological Progress and (Un)employment Development - Uwe Blien; Oliver Ludewig (Institute of Labor Economics (IZA), 2017)
In recent times the employment effects of technical progress raised much intention. Will recent productivity gains lead to technological unemployment or to a new prosperity? In our paper it is shown formally that under general and standard preconditions the price elasticity of demand on product markets is decisive: Technological progress leads to an expansion of employment if product demand is elastic. It is accompanied, however, by shrinkage of employment if product demand is inelastic. A transition from the elastic into the inelastic range of the demand function for the most important product(s) can already suffice to plunge a region into crisis. In our empirical analysis we use industry level time series data on output, prices, employment and national income for Germany provided by the Federal Statistical Office. We estimate Marshallian type demand functions using an instrumental variables estimator to derive the price elasticities for different industries and link this information to the regional labour market performance of the respective industries and regions.
Keywords: Q33; R11; J23; 330; labour market dynamics; productivity growth; structural change